Komodo National Park Destination Marketing Strategy In Increasing Tourist Visit Numbers - Hastuti, Siti Sri Wahyu; Rahmi, siti Atika; Eikman, Alfian; Selva, Selva (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Marketing strategy is an important aspect in increasing the number of tourist visits. In this research, the marketing strategy is carried out by the Komodo National Park, namely a conservation area. Marketing strategies, namely promotional strategies, are very important for visitors who visit Komodo National Park. The research method is qualitative research using primary and secondary data. The results of the research are marketing strategies seen from promotional strategies to increase the number of visitors visiting Komodo National Park.